2016
DOI: 10.1111/tbj.12702
|View full text |Cite
|
Sign up to set email alerts
|

Benign Papillomas of the Breast Diagnosed on Large-Gauge Vacuum Biopsy compared with 14 Gauge Core Needle Biopsy - Do they require surgical excision?

Abstract: To evaluate whether biopsy with vacuum-assisted biopsy (VAB) devices improves histologic underestimation rates of benign papillomas when compared to smaller bore core needle biopsy (CNB) devices. Patients with biopsy-proven benign papillomas with surgical resection or minimum 12 months follow-up were selected. Two breast pathologists reviewed all pathology slides of percutaneous and excisional biopsy specimens. Histologic underestimation rates for lesions biopsied with 10-12 Gauge (G) VAB were compared to thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
2
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 44 publications
0
17
2
2
Order By: Relevance
“…50% No association with age and size lesion Ko et al 2017 [ 63 ] n = 346 PL in CNB Upgrade In VAB ( n = 211) In OE ( n = 135) Upgrade Overall in 2.3% If size < 1cm: 0.9% Size of PL correlates with upgrade Close follow-up with ultrasound instead of excision Moon et al 2016 [ 64 ] n = 65 PL in CNB Upgrade In VAB ( n = 12) In OE ( n = 53) Upgrade In OE in 9% (5/53) In VAB 8% (1/12) No recommendation Niinikoski et al 2018 [ 65 ] n = 80 PL in CNB Small PL in selected patients-OE can be avoided Pareja et al. 2016 [ 66 ] Upgrade in OE ( n = 171) after PL Without atypia In CNB Upgrade In OE 2.3% (4/171) Regardless of size, observation is appropriate at radiologic–pathologic concordant CNB Seely et al 2017 [ 67 ] n = 107 PL in OE Upgrade after VAB ( n = 60) CNB ( n = 47) Upgrade in OE After VAB in 1.6% (1/60) After CNB in 8.5% (4/47) Higher upgrade in OE if PL is diagnosed on CNB Tatarian et al 2016 [ 68 ] n = 16 PL in CNB Upgrade in OE Upgrade in OE In 2/16 cases (12.5%) Surgical excision should be considered in patients with benign papillomas Tran et al 2017 [ 69 ] n = 43 PL in CNB Upgrade in OE Upgrade in OE In 1/43 cases (2%) Low-upgrade rate in OE Wyss et al 2014 [ 70 ] …”
Section: Resultsmentioning
confidence: 99%
“…50% No association with age and size lesion Ko et al 2017 [ 63 ] n = 346 PL in CNB Upgrade In VAB ( n = 211) In OE ( n = 135) Upgrade Overall in 2.3% If size < 1cm: 0.9% Size of PL correlates with upgrade Close follow-up with ultrasound instead of excision Moon et al 2016 [ 64 ] n = 65 PL in CNB Upgrade In VAB ( n = 12) In OE ( n = 53) Upgrade In OE in 9% (5/53) In VAB 8% (1/12) No recommendation Niinikoski et al 2018 [ 65 ] n = 80 PL in CNB Small PL in selected patients-OE can be avoided Pareja et al. 2016 [ 66 ] Upgrade in OE ( n = 171) after PL Without atypia In CNB Upgrade In OE 2.3% (4/171) Regardless of size, observation is appropriate at radiologic–pathologic concordant CNB Seely et al 2017 [ 67 ] n = 107 PL in OE Upgrade after VAB ( n = 60) CNB ( n = 47) Upgrade in OE After VAB in 1.6% (1/60) After CNB in 8.5% (4/47) Higher upgrade in OE if PL is diagnosed on CNB Tatarian et al 2016 [ 68 ] n = 16 PL in CNB Upgrade in OE Upgrade in OE In 2/16 cases (12.5%) Surgical excision should be considered in patients with benign papillomas Tran et al 2017 [ 69 ] n = 43 PL in CNB Upgrade in OE Upgrade in OE In 1/43 cases (2%) Low-upgrade rate in OE Wyss et al 2014 [ 70 ] …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the management of benign IDPs diagnosed by CNB remains controversial. Several studies have shown that the upgrading rate after open excision is associated with the adequacy of samples in biopsy lesions, even though the needle gauge used in CNB plays an important role in upgrading the rate of IDP [15,16]. In our study, we found an underestimation of 2/26 (7.7%) following open excision after VAE.…”
Section: Discussioncontrasting
confidence: 50%
“…In such cases, T2‐hypo‐rim may indicate the possibility that the lesion is intraductal/intracystic. Furthermore, papillary lesions are often difficult to correctly diagnose by the analysis of small‐volume histopathologic specimens, particularly those obtained by small‐gauge CNB . Maxwell et al reported that 11 (11%) of 96 lesions with a 14‐gauge CNB diagnosis of benign papilloma without atypia were upgraded to atypia or malignancy after subsequent lesion excision by either VAB or surgery.…”
Section: Discussionmentioning
confidence: 99%